A dynamic meiotic SUN belt includes the zygotene-stage telomere bouquet and is disrupted in chromosome segregation mutants of maize (Zea mays L.) - Murphy, Shaun P.; Gumber, Hardeep K.; Mao, Yunyun; Bass, Hank W. (Frontiers in Plant Science, 2014)
The nuclear envelope (NE) plays an essential role in meiotic telomere behavior and links the cytoplasm and nucleoplasm during homologous chromosome pairing and recombination in many eukaryotic species. Resident NE proteins including SUN (Sad-1/UNC-84) and KASH (Klarsicht/ANC-1/Syne-homology) domain proteins are known to interact forming the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex that connects chromatin to the cytoskeleton. To investigate the possible cross-kingdom conservation of SUN protein functions in plant meiosis, we immunolocalized maize SUN2 using 3D microscopy of pollen mother cells from maize (Zea mays L.), a large-genome plant model with a canonical NE zygotene-stage telomere bouquet. We detected SUN2 at the nuclear periphery and found that it exhibited a distinct belt-like structure that transitioned to a half-belt during the zygotene stage and back to a full belt during and beyond the pachytene stage. The zygotene-stage half-belt SUN structure was shown by 3D immuno-FISH to include the NE-associated telomere cluster that defines the bouquet stage and coincides with homologous chromosome synapsis. Microtubule and filamentous actin staining patterns did not show any obvious belt or a retracted-like structure other than a general enrichment of tubulin staining distributed widely around the nucleus and throughout the cytoplasm. Genetic disruption of the meiotic SUN belt staining patterns with three different meiosis-specific mutants, desynaptic (dy1), asynaptic1 (as1), and divergent spindle1 (dv1) provides additional evidence for the role of the nuclear envelope in meiotic chromosome behavior. Taking into account all of the observations from this study, we propose that the maize SUN belt is directly or indirectly involved in meiotic telomere dynamics, chromosome synapsis, and possibly integration of signals and forces across the meiotic prophase nuclear envelope.